Labor-Force Heterogeneity and Asset Prices: The Importance of Skilled Labor - Belo, Frederico; Li, Jun; Lin, Xiaoji; Zhao, Xiaofei (Review of Financial Studies, 2017)
Previous studies have identified a negative relation between firms’ hiring rates and future stock returns in the cross-section. We document that this relation is significantly steeper in industries that rely relatively more on high-skill workers than low-skill workers. A long-short portfolio sorted on firm-level hiring rate earns an average annual return of 8.6% in high-skill industries, and only 0.9% in low-skill industries. Moreover, this pattern is not explained by the standard CAPM. These findings are consistent with a neoclassical model with labor force heterogeneity and labor market frictions if it is more costly to replace high-skill than low-skill workers. Received August 14, 2015; editorial decision December 31, 2016 by Editor Leonid Kogan.